Human UPF3A and UPF3B enable fault‐tolerant activation of nonsense‐mediated mRNA decay - Wallmeroth, Damaris; Lackmann, Jan-Wilm; Kueckelmann, Sabrina; Altmüller, Janine; Dieterich, Christoph; Böhm, Volker; Gehring, Niels H. (The EMBO journal, 2022)
The paralogous human proteins UPF3A and UPF3B are involved in recognizing mRNAs targeted by nonsense‐mediated mRNA decay (NMD). UPF3B has been demonstrated to support NMD, presumably by bridging an exon junction complex (EJC) to the NMD factor UPF2. The role of UPF3A has been described either as a weak NMD activator or an NMD inhibitor. Here, we present a comprehensive functional analysis of UPF3A and UPF3B in human cells using combinatory experimental approaches. Overexpression or knockout of UPF3A as well as knockout of UPF3B did not substantially change global NMD activity. In contrast, the co‐depletion of UPF3A and UPF3B resulted in a marked NMD inhibition and a transcriptome‐wide upregulation of NMD substrates, demonstrating a functional redundancy between both NMD factors. In rescue experiments, UPF2 or EJC binding‐deficient UPF3B largely retained NMD activity. However, combinations of different mutants, including deletion of the middle domain, showed additive or synergistic effects and therefore failed to maintain NMD. Collectively, UPF3A and UPF3B emerge as fault‐tolerant, functionally redundant NMD activators in human cells.